2010
DOI: 10.1158/0008-5472.can-09-4040
|View full text |Cite|
|
Sign up to set email alerts
|

A Small Interfering RNA Screen of Genes Involved in DNA Repair Identifies Tumor-Specific Radiosensitization by POLQ Knockdown

Abstract: The effectiveness of radiotherapy treatment could be significantly improved if tumour cells could be rendered more sensitive to ionizing radiation without altering the sensitivity of normal tissues. However many of the key, therapeutically exploitable mechanisms that determine intrinsic tumour radiosensitivity are largely unknown. We have conducted a siRNA screen of 200 genes involved in DNA damage repair aimed at identifying genes whose knockdown increased tumour radiosensitivity. Parallel siRNA screens were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
116
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 38 publications
5
116
0
Order By: Relevance
“…We anticipate that ectopic activation of TMEJ may be of high clinical significance, also considering the recent finding that Polymerase Theta upregulation is associated with poor survival in cancer 35,36 ; if not properly controlled, POL y's ability to tie DNA ends together can have very undesirable effects, as it provides cells with the means to proliferate in the presence of increased replication stress 37 . Blocking this activity may thus constitute a potent strategy towards preventing cancerous growth.…”
Section: Discussionmentioning
confidence: 96%
“…We anticipate that ectopic activation of TMEJ may be of high clinical significance, also considering the recent finding that Polymerase Theta upregulation is associated with poor survival in cancer 35,36 ; if not properly controlled, POL y's ability to tie DNA ends together can have very undesirable effects, as it provides cells with the means to proliferate in the presence of increased replication stress 37 . Blocking this activity may thus constitute a potent strategy towards preventing cancerous growth.…”
Section: Discussionmentioning
confidence: 96%
“…After treatment with various DNA-damaging agents, RUVBL1 is required for the dephosphorylation of phosphorylated histone H2AX, a marker of DNA double-strand breaks (DSBs), through the histone acetyltransferase activity of TIP60 [8]. Likewise, depletion of RUVBL2 increases the persistence of phosphorylated histone H2AX upon treatment with X-rays [10]. Apart from the pathway involving the TIP60 complex, RUVBLs regulate the abundance and activity of phosphatidylinositol 3-kinases such as ataxia telangiectasia mutated (ATM), ATM-and Rad3-related (ATR) kinase, and DNA-dependent protein kinase (DNA-PK) that sense and activate the DNA damage signal [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the data are varied, some studies have suggested that HR-defective cell lines and xenografts can be more sensitive to ionizing radiation (IR), cisplatin, mitomycin C (MMC), etoposides, melphalan and poly(ADP-ribose) polymerase inhibitors (PARPi). 6,7 These cell lines, however, have also been reported to be variably sensitive or even resistant to taxane-based chemotherapy (e.g., docetaxel). [8][9][10][11][12][13][14][15][16][17] These data suggest that patients with a BRCA2 mutation with tumours defective in HR may be targeted by agents, such as RT, cisplatin, anthracyclines or PARPi.…”
Section: Introductionmentioning
confidence: 99%